On the Difficulty of Being Good - Załuski, Wojciech (Roczniki Filozoficzne, 2025)
The question of whether human beings are more prone to do evil or good is typically framed in psychological terms, focusing on human predispositions to determine whether “evil” tendencies outweigh “good” ones, or vice versa. This approach has given rise to a variety of views on human nature, ranging from the two classical extremes—the Hobbesian view, which holds that humans are inherently evil, to the Rousseauian view, which sees them as intrinsically good—to more nuanced positions situated between these poles. In this paper, a different line of inquiry is proposed: instead of approaching the issue from the perspective of the subject (i.e., human predispositions), it is examined from the standpoint of the object—the nature of good and evil themselves. The thesis is advanced that if human beings are indeed more inclined to do evil than good, the explanation may lie not only in their psychology, but also in the very structure and character of good and evil—specifically, in the fact that good actions are more difficult to perform than bad ones. The nature of this difficulty is also explored in the paper by analyzing both the external and internal aspects of human actions.